Gait screening of a population of young, healthy athletes by means of a portable, low-cost device unveils hidden left–right asymmetries in both quadriceps and anterior cruciate ligament forces - Nicolò Colombo; Francesca Vignaga; Eleonora Solari; Mattia Merlo; Alessandro Manelli; Daniela Negrini; Andrea Moriondo (BMC Research Notes, 2019)
Abstract Objective The present study reports the on-field screening of a population of young soccer players in the pursuit of alterations in gait using a portable and low-cost gait analysis system composed of a Wii Balance Board and a webcam. Results Recordings of motion of the lower extremities along with vertical ground reaction force (GRF) were used to quantify coefficients of symmetry for the overall GRF and the forces exerted by the quadriceps femori and acting on the anterior cruciate ligament (ACL). Data show that, in face of a quite homogeneous symmetry of GRF during left and right stance phases of gait, quadriceps and ACL exert and are subjected to left–right asymmetrical forces that might prelude, especially in young athletes, later alterations of gait.